2018
DOI: 10.7759/cureus.2704
|View full text |Cite
|
Sign up to set email alerts
|

Clinico-epidemiological Characteristics of Corrosive Ingestion: A Cross-sectional Study at a Tertiary Care Hospital of Multan, South-Punjab Pakistan

Abstract: IntroductionCorrosive ingestion is a grave public health problem. It is a medical emergency and shows diverse clinical presentations. The ingestion of corrosive substances has devastating effects on upper gastrointestinal and respiratory tracts and the corrosive injury is associated with numerous life-threatening complications. The present study aims to explore the clinico-epidemiological characteristics of patients of corrosive ingestion presenting at a tertiary care hospital of Multan, Pakistan.MethodThe tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 25 publications
1
11
1
1
Order By: Relevance
“…In contrast to the result of the current study, Hashmi et al (2018) in their study at a Tertiary Care Hospital of Multan, South-Punjab, Pakistan ;reported that females are more vulnerable to corrosive poisoning than males as corrosive agent were present at home for cleaning and washing purposes and women are more interested in cleaning compared to men.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to the result of the current study, Hashmi et al (2018) in their study at a Tertiary Care Hospital of Multan, South-Punjab, Pakistan ;reported that females are more vulnerable to corrosive poisoning than males as corrosive agent were present at home for cleaning and washing purposes and women are more interested in cleaning compared to men.…”
Section: Discussioncontrasting
confidence: 99%
“…About the most common symptoms affecting the patients; the present work revealed that GIT symptoms combined with respiratory manifestations were the most common one (statistically significant) (Table 3). Hashmi et al (2018) reported that GIT symptoms were the most common symptoms than the respiratory due to the highly effective protective mechanism of the pharynx and glottis. Also, Vezakis et al (2016) found that GIT symptoms predominate.…”
Section: Discussionmentioning
confidence: 99%
“…Экспериментальные модели химического ожога пищевода (ХОП) щелочами мало изучены и не имеют четкого морфологического подтверждения. На современном этапе одной из основных проблем при выполнении эксперимента является сложность дозировки химического агента и, как следствие, большой процент гибели животных на этапе нанесения травмы [6][7][8].…”
Section: Introductionunclassified
“…In developing countries, the incidence of corrosive ingestion is significantly higher and, in most cases, remains unreported [2]. Their actual prevalence cannot be assumed from random observations and personal judgments of healthcare professionals [10].…”
Section: Introductionmentioning
confidence: 99%
“…Corrosive ingestion includes the ingestion of substances with extremes of pH and is a grave public health problem across the globe. It can be seen in both developed and developing countries, but it is more common in developing countries [ 1 , 2 ]. Sulphuric acid, hydrochloric acid, oxalic acid, sodium hydroxide, potassium hydroxide, and bleaches are some of the most commonly used corrosive materials and are found in drain cleaners, various cleaning agents, dishwasher detergents, hair relaxers, and disk batteries [ 3 ].…”
Section: Introductionmentioning
confidence: 99%